Potencialidades e limites do ensino de projeto arquitetônico: um estudo sobre diferentes modalidades de ateliês - Luz, Carolina Nóbrega Sabóia (2024)
This thesis presents an research about the different types of teaching studio that exist nowadays: face-to-face, virtual, remote and hybrid, and about their impact on teaching/learning. The studio, a privileged space where the teaching/learning of Architecture and Urbanism Courses has been changing over time, both physically and pedagogically including practices and methodological strategies. More recently, with the spread of the internet and social networks, new types of studios have emerged, virtual, remote and hybrid, in addition to those in the distance learning courses modality. Thus, considering the current post-pandemic context, the central questions of this research are: How does each type of studio - face-to-face, virtual, remote and hybrid, impact on the teaching of architectural design? And in which of these modalities does the potential overcome the limits in the teaching/learning process of architectural design in the contemporary post-pandemic context? The main objective is then to evaluate in which type of project studio - face-to-face, virtual, remote or hybrid, the potential exceeds the limits in the teaching/learning process of architectural design, in public universities in Northeastern Brazil, following the quality precepts defended by entities in the field of Architecture and Urbanism. Among these are the development of perception of environments and practical and reflective learning. In the methodological field, it is a predominantly qualitative research that uses multiple case studies as a method. The research context took place of Architecture and Urbanism Courses in UFRN, UFC and UFPB. There were six cases studied: remote studio – UFRN and UFC, face-to-face studio – UFRN and UFC, hybrid studio – UFPB and virtual studio – UFRN. Analytical scripts were prepared with the aspects to be observed at each stage of the research: documentary analysis of the Pedagogical Political Projects and course plans, direct observation of classes, questionnaires applied to students and interviews with teachers. Data will be analyzed and interpreted using the thematic analysis proposed by Minayo. In summary, we found that each studio model presents favorable and unfavorable aspects for project learning; however, the face-to-face studio was the one that had the greatest number of potentialities and the remote studio was the format in which there was greater mention of limits. The resources and pedagogical practices intrinsic to remote and virtual teaching largely permeate its own studio format, when implemented in the face-to-face studio, now renewed by the more frequent use of ICTs, being the modality in which the potential most exceeds the limits in teaching architectural design in the post-pandemic context. Finally, it is concluded that the various pedagogical practices, approaches, methodologies, teaching models and assessments used in architectural design studios depend less on the studio format taught than on the skills and competence of the teacher who conducts it. The results obtained can contribute to improving the project's teaching/learning, supporting teaching plans for Architecture and Urbanism Courses teachers from various universities in the country, and even from other countries.